Nutritional status and anxiety levels of adolescent during COVID-19 pandemic - Indriawati, Ratna; Susyanto, Bambang Edi; Amany, Farah Dita; Wibowo, Tunjung (Intelektual Pustaka Media Utama, 2025)
The COVID-19 pandemic has had various health impacts, experienced by all age groups. However, many health problems are experienced by adolescents. The nutritional and psychological issues of teenagers during the COVID-19 pandemic require additional investigation. This study seeks to investigate the nutritional status and anxiety levels of teenagers during the COVID-19 pandemic. The cross-sectional research. Boys and girls aged 14-18 years became the research subject, who was chosen by using incidental sampling. The independent variable is nutritional status. The variable is anxiety. The data was collected by distributing a questionnaire, the assessment of nutritional status using body mass index, and self-rating anxiety scale (SAS/SRAS) for psychological status. It reported that there is no influence between nutritional status and anxiety in adolescents (p>0.05). There is no influence between nutritional status and anxiety in adolescents.